Responsible Urban Innovation Working with Local Authorities a Framework for Artificial Intelligence (AI) - Ida Farida; Wahyu Ningsih; Ninda Lutfiani; Qurotul Aini; Eka Purnama Harahap (Universitas Negeri Semarang, 2023)
Purpose: By demonstrating that by adopting the principles of responsible urban innovation, we can harness the potential of digital technology to address urbanization issues and can minimize potential negative impacts.Methods: The paper proposes a conceptual framework for accountable urban innovation, focusing on government AI systems, and draws on a literature review, practical examples, and research. The authors argue that responsible urban innovation must balance the costs, benefits, risks, and impacts of developing, implementing, and using AI systems in local government management. This approach emphasizes the importance of achieving desired urban outcomes while ensuring accountability.Results: The framework provides potential directions for future research and development, offering an overview of recognized topics and a schedule for analysis. This research may assist urban managers, planners, and decision-makers in understanding the critical role that government AI systems play in achieving accountable outcomes. By adopting responsible urban innovation principles, we can harness the potential of digital technology to address urbanization issues while minimizing potential negative impacts.Novelty: The conceptual framework presented in this study offers a new view in understanding the role of local government AI systems in achieving accountable outcomes.